Hungarian Monitoring, 27 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Polish premier Mazowieckzi gives interview to Hungarian Radio - GDR refugees Domestic Affairs: - On Gyula Horn's instructions, Hungarian consul in Prague also takes part in legal defense of two detained young men - Opposition protests against the Workers' Militia - Mass held in front of Gellért Hill's Sziklakápolna (Cliff Chapel) for the first time in 40 years - Calvinist minister László Tőkés answers questions from his private telephone - Independent Lawyers' Forum thinks it scandalous that a small section of Hungarian Socialist Workers' Party (MSZMP) is trying to turn the Party's "public property" into private property for itself Economy: - Independent Smallholders Party demands complete cessation of state support for loss-making large companies Külpolitika: - Mazowieckiz lengyel miniszterelnök interjúja a Magyar Rádiónak - NDK menekültügy Belpolitika: - Horn Gyula utasítására a prágai magyar konzul is részt vesz a két letartóztatott fiatalember jogi védelmében - Ellenzéki tiltakozások a Munkásőrség ellen - Budapesten 4o év óta először celebráltak misét a Gellért-hegyi Sziklakápolna előtti téren - Kérdések Tőkés László református lelkipásztorhoz, amelyekre magántelefonon keresztül válaszol - A Független Jogászfórum botrányosnak tartja, hogy az MSZMP egy szúk köre a párt eddigi, társadalmi tulajdonnak nevezhető vagyonát magánvagyonná alakítva törekszik átmenteni Gazdaság: - Az FKGP követeli, hogy teljesen szüntessék meg a veszteséges nagyvállalatok állami támogatását